The portrayal of unfaithful wives in Philippine cinema from the 1980's up to 2010's - JESSICA KANE, SALAO (Archīum Ateneo, 2013)
This thesis discusses the portrayal of Filipino women in Filipino films in their roles as unfaithful wives, and explores whether this portrayal shapes perspectives in giving roles of women more significance. Through the framing of messages, the films are